PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT TAKEDA INDONESIA - Muhammad Rozali; Kusnadi Kusnadi (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This research was conducted at Pharmaceutical company PT Takeda Indonesia with the problem that the company was based on initial observations of motivation, compensation, and employee performance, especially in the sales division showing the level of employee motivation was still low, and it is also found that most employees were less satisfied with the compensation system in effect, so that the level of employee performance in PT Takeda Indonesia’s sales division has not been optimal. The purpose of this study is to determine and analyze the effect of motivation and compensation on employee’s performance in PT. Takeda Indonesia. The method used in this study is descriptive quantitative and associative methods. The sample in this study was obtained through a response from 53 employees of PT. Takeda Indonesia in Team Established. The questionnaire was designed in such a way by using a Likert scale to obtain data from the three research variables namely motivation, compensation, and employee performance. Data analysis was done using Multiple Linear Regression with SPSS 18.00 program tools. The results show that motivation and compensation affect the performance of employees at PT. Takeda Indonesia, both jointly and partially.